2021
DOI: 10.1093/jas/skab330
|View full text |Cite
|
Sign up to set email alerts
|

Live yeast and yeast extracts with and without pharmacological levels of zinc on nursery pig growth performance and antimicrobial susceptibilities of fecal Escherichia coli

Abstract: A total of 360 weanling barrows (Line 200 ×400, DNA, Columbus NE; initially 5.6 ± 0.03 kg) were used in a 42-d study to evaluate yeast-based pre- and probiotics (Phileo by Lesaffre, Milwaukee, WI) in diets with or without pharmacological levels of Zn on growth performance and antimicrobial resistance (AMR) patterns of fecal Escherichia coli. Pens were assigned to 1 of 4 dietary treatments with 5 pigs per pen and 18 pens per treatment. Dietary treatments were arranged in a 2 × 2 factorial with main effects of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Post-weaning diarrhea (PWD) is one of the most common causes of stunted growth and mortality in piglets, causing huge economic losses to the pig industry. In practice, ZnO at pharmacological doses (2,000 mg Zn/kg or more) is widely applied to weaned piglet diets to prevent occurrences of PWD ( 3 , 26 ). In our study, dietary TBZC supplementation significantly reduced the diarrhea incidence in piglets, and its effect was comparable to that of the ZnO treatment group, which supports the previous finding that low-dose TBZC could effectively replace pharmacological doses of ZnO to alleviate diarrhea ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Post-weaning diarrhea (PWD) is one of the most common causes of stunted growth and mortality in piglets, causing huge economic losses to the pig industry. In practice, ZnO at pharmacological doses (2,000 mg Zn/kg or more) is widely applied to weaned piglet diets to prevent occurrences of PWD ( 3 , 26 ). In our study, dietary TBZC supplementation significantly reduced the diarrhea incidence in piglets, and its effect was comparable to that of the ZnO treatment group, which supports the previous finding that low-dose TBZC could effectively replace pharmacological doses of ZnO to alleviate diarrhea ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, many swine and poultry studies have demonstrated that probiotics help to develop healthy microflora (mainly probiotics), which prevent pathogen adhesion and invasion of intestinal epithelial cells, induce the production of antibacterial compounds, maintain epithelial barrier integrity, and regulate metabolism and immune system ( Wang et al, 2019 ; Šikić Pogačar et al, 2020 ; Chance et al, 2021 ). However, there is little evidence that ruminant-derived probiotics regulate gut microbial composition and thus affect metabolism to promote beef cattle body weight.…”
Section: Introductionmentioning
confidence: 99%
“…The ordinal nature of this data makes sample size calculation difficult, thus, fecal DM may be a more suitable response to evaluate. Despite only one ETEC challenge study using the fecal DM approach, there are other published papers in nonchallenged pigs where fecal DM analysis was conducted ( Chance et al, 2021 ; Laskoski et al, 2021 ). Because these data are quantitative, they are typically presented in a form that allows scientists to extract measures of variability and means needed for sample size calculation.…”
Section: Resultsmentioning
confidence: 99%